A comparison between fine-needle biopsy and fiberoptic bronchoscopy in patients with lung lesions. Issue 3 (May 1974) - Borgeskov, Sven; Francis, Dorthe
Abstract : Borgeskov, S. and Francis, D. (1974). Thorax, 29, 352-354. A comparison between fine-needle biopsy and fiberoptic bronchoscopy in patients with lung lesions. We present a series of 40 patients with lung lesions in whom a specific diagnosis was not obtained by conventional methods of examination and in whom tumour was not visualized directly by bronchoscopy with a flexible bronchoscope. Bronchial brushing and blind biopsy-taking were performed and the results were compared with those of fine-needle aspiration biopsy. The percentage of diagnoses for the two methods was 30 and 62 respectively. In 40% of cases the diagnosis was obtained solely by fine-needle aspiration biopsy and in 10% alone with the aid of the flexible bronchoscope.